2019
DOI: 10.1093/icesjms/fsz124
|View full text |Cite
|
Sign up to set email alerts
|

Long-term measurements of fish backscatter from Saildrone unmanned surface vehicles and comparison with observations from a noise-reduced research vessel

Abstract: Two Saildrone unmanned surface vehicles (USVs) were instrumented with echosounders and deployed in the Bering Sea to make acoustic observations of walleye pollock for 103 days. The Saildrones proved to be a suitable platform for measurement of fish backscatter: they produced high-quality measurements at wind speeds of <10 m s−1. Pollock backscatter measured from the Saildrones was compared to backscatter measured by a noise-reduced research vessel during two “follow-the-leader” comparisons. In a locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…The first two hypotheses could explain why the depths are not consistent but not the presence of a consistent bias. The third hypothesis is unlikely as, to our knowledge, no deepening of scattering layers at such depths was reported (De Robertis & Handegard, 2013;De Robertis et al, 2019;Ona et al, 2007;Peña, 2019). The fourth hypothesis cannot be rejected and is discussed further below.…”
Section: Naames Observationsmentioning
confidence: 75%
“…The first two hypotheses could explain why the depths are not consistent but not the presence of a consistent bias. The third hypothesis is unlikely as, to our knowledge, no deepening of scattering layers at such depths was reported (De Robertis & Handegard, 2013;De Robertis et al, 2019;Ona et al, 2007;Peña, 2019). The fourth hypothesis cannot be rejected and is discussed further below.…”
Section: Naames Observationsmentioning
confidence: 75%
“…In the study region, acoustic backscatter is dominated by scattering from pollock (De Robertis et al 2019), the northern fur seal's primary prey when foraging on the Bering Shelf (Zeppelin & Ream 2006). Acoustic-trawl surveys conducted from a research vessel in July 2016 confirmed that acoustic backscatter could be primarily attributed to pollock (De Robertis et al 2019).…”
Section: Saildrone Location Acquisition and Data Collectionmentioning
confidence: 90%
“…This feasibility study occurred during a largescale, ecosystem-based research mission to map walleye pollock Gadus chalcogrammus ('pollock') abundance and depth distribution in the fur seal's foraging range (Mordy et al 2017, De Robertis et al 2019. The aim was to follow an individual for 2 d and collect data on oceanographic conditions and prey availability along the foraging path.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations